Jual Beli Ternak Dengan Sistem Blante Pada Pasar Tradisional Hewan Di Kawangkoan Menurut Hukum Adat Minahasa - Refly Umbas; Sondakh, Jemmy; Ronny Sepang (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The purpose of the research is to find out, How is the existence of the buying and selling system in the traditional animal market in Kawangkoan according to Minahasa customary law; What are the characteristics of the form of agreement including the compliance of traders to the agreement and the resolution of disputes that occur. By using the empirical normative legal research method, the research was conducted focused on the study of law related to the application of the customary law system in Minahasa in buying and selling in traditional markets. The results of the study; a. a buying and selling model was found with a blante system applied in traditional markets, in the form of open and cash barter; b. Every agreement is binding according to custom and is carried out honestly by both parties if there is a shortage it is borne together; c. Dispute resolution if there are traders who commit fraud and deception will be reported to the market foreman to be prosecuted and removed and not allowed to trade in the Kawangkoan Market.